The Tragic Image of Blanche Du Bois in Tennessee Williams' Play A Streetcar Named Desire (Journal of the College of Basic Education, 2023)
The American playwright Tennessee Williams (1911-1983) was raised up by a violent, hard, drinking father, but an affectionate loving mother, a caring grandmother, and a devoted elder sister. This situation made Williams sympathize with the feminine figures in his family.The tragedy of his elder sister, that concluded with her untimely death, influenced his life and was reflected in most of his future writings including his play A Streetcar Named Desire.This paper traces the downfall of a modern woman called Blanche Du Bois (the protagonist of A Streetcar Named Desire.), trying to determine whether the writer intended to portray this character as a 'classical tragic heroine', or not.Blanche's crises begin with her husband's death and the acceleration of life's bad circumstances, in addition to her inability to control her desires; that culminated in losing her job. Dreaming of revitalizing her hopes in life, she decides to take refuge in her sister's house. Upon discovering her dishonorable past, her brother -in-law humiliates and blackmails her; which drives her insane.By applying the classical rules of tragedy to this play, we notice that it contains most of the essential elements of classical tragedies .Nevertheless, the protagonist of this play does not appear to qualify as a tragic heroine in the Aristotelian sense. Yet, judging Blanche and her dilemma according to the classical conventions of tragedy might do them great injustice. One should keep in mind that life, human nature, and literature have changed dramatically since Aristotle's days. What used to be considered a heroic deed at that time might seem foolish nowadays. Consequently, we should expect that people's view of life and themselves has become radically different as well. Therefore, the presence of authentic classical tragic heroes in modern literature seems to have become inconvenient. What we might encounter at best, is a modern ordinary tragic figure that arouses pity- precisely like Blanche